Dampak non-target dari pengendalian hayati spesies asing terhadap ekosistem - Damayanti Buchori (Jurnal Entomologi Indonesia, 2007)
Non target impact of classical biological control of exotic species in the ecosystem. Classical biological control has been hailed as a successful control method of many exotic species of pests. However, recently this method of control has been questioned due to several cases of non target impact. Non target impact can occur two ways, i.e. direct non target impact when there is a host shift of the bioagents (e.g. changes in preferences), and the indirect non target impact which can occur through, among others, food web subsides that will change the overall interactions of many species within an ecosystem. The aim of this paper is to understand the interactions between introduced exotic agents (e.g. insects) toward local diversity, e.g. what are the implications of the interactions toward local biodiversity? Are there non target and indirect impacts of these introductions in Indonesia? The discussions covers the concept of biological control and conservation issues that should be taken into consideration, particularly in the context of insect conservation and impacts of classical biological control on island diversity.